A Chinese family of autosomal recessive polycystic kidney disease identified by whole exome sequencing. Issue 22 (29th May 2020) - Zhang, Jun; Dai, Li-meng; Li, Fu-rong; Zhang, Bo; Zhao, Jing-hong; Cheng, Jin-bo
Abstract: Background: Autosomal recessive polycystic kidney disease (ARPKD) is an autosomal recessive hepatorenal fibrocystic syndrome. The majority of ARPKD patients progress to end-stage renal disease. Precise molecular diagnosis of ARPKD has proven valuable for understanding its mechanism and selecting optimal therapy. Methods: A Chinese family with ARPKD was recruited in current study. The clinical characteristics of ARPKD patient were collected from medical records and the potential responsible genes were studied by the whole exome sequencing (WES). Candidate pathogenic variants were validated by Sanger sequencing. Results: Both renal manifestation and hepatobiliary phenotype were observed. WES revealed compound heterozygous mutations of polycystic kidney and hepatic disease 1 genes, NM_138694: c.751G>T, (p.Asp251Tyr) and c.3998_4004delACCTGAA (p.Asn1333Thr fs × 13), which were confirmed by Sanger sequencing. Moreover, the mutations in the proband and its affected sib were co-segregated with the phenotype. Conclusions: The novel mutation in polycystic kidney and hepatic disease 1 gene identified by WES might be molecular pathogenic basis of this disorder.